Millennial learners’ acceptance and satisfaction of blended learning environment / Sharidatul Akma Abu Seman … [et al.] - Abu Seman, Sharidatul Akma; Hashim, Maryam Jameelah; Mohd Roslin, Rosmimah; Mohd Ishar, Nor Irvoni (2018)
Teaching in an era dominated by millennials represents a challenging task for educators in Institutes of Higher Learning (IHLs). One distinct feature in teaching millennials is the advancement in digital learning which has improved learning styles in higher education. Besides face-to-face interactions with the instructors, the blended learning approach has been introduced in many courses to cater to the needs of millennial learners. This study aims to provide an insight into on students’ acceptance and satisfaction towards the use of Learning Management System (LMS) in a blended learning environment. An online survey was administered to 167 respondents. The majority of the respondents are below 22 years of age and first-year students who are fresh and new to the blended learning concept. This study measured factors like technology experience, computer anxiety, service quality, system quality, information quality, course quality, and instructor to determine the students’ overall satisfaction. The model was analysed using the partial-leastsquares structural modeling approach. The result shows that service quality, instructor quality, and course quality are among the critical factors towards students’ acceptance and satisfaction. Therefore, to ensure LMS’s effectiveness and students’ satisfaction, decisionmakers at the higher institution should consider these factors before implementing a blended learning initiative via LMS as the platform.